RELATIONS SHOW TELEVISIONS THAT A AFFECT DELAY TALK (SPEECH DELAY) ON TODDLER IN GRAHA GROWIG DEVELOPMENG JOMBANG, (STUDIES IN GRAHA GROWING DEVELOPMENT ,DISTRICT JOMBANG) - SW, Ruliati Indah (Well Being, 2018)
Parents' anxiety will increase if they know that their child is experiencing a delay in talking compared to his age. This will eventually invite questions, so parents will come to the psychologist. This speech and language delay detection must be done early with the right method. The purpose of this study to know the effect of watching television with speech delay (speech delay) in toddlers in Graha Tumbuh Kembang Jombang. The research used cross sectional correlation analytic, the population used were all children under five who experienced speech delay in Graha Tumbuh Kembang Jombang Clinic as many as 55 people, with sample number 48 people using consecutive sampling technique, independent variable ie watching television, while the dependent variable ie delay talk to toddlers. Data collection using questionnaires and observation sheets, data analysis using mann whitney test. Mann whitney test analysis results obtained ρ = 0,000 <0.05 which means there is a relationship with the delay television talk show. The conclusion from the research results that watching television affects the delay talk. Long time watching television, inappropriate selection of television shows as well as parental guidance in menonon teevisi affect the delay talk to toddlers.